GENE-29. DLL3 AND ETV1 ARE INACTIVATED/METHYLATED IN CIC WILD-TYPE, IDH-MUTATED, 1p/19q-CODELETED GLIOMA. (5th November 2018) - Kosel, Matthew; Lachance, Daniel; Decker, Paul; Kollmeyer, Thomas; Caron, Alissa; Drucker, Kristen; Sarkar, Gobinda; Knight, Andrew; Halder, Chandralekha; Tian, Shulan; Abyzov, Alexej; Burns, Terry; et al.
Abstract: Adult diffuse glioma that harbor IDH mutation and 1p/19q codeletion commonly have CIC mutations; however, the functional and prognostic significance of CIC mutations remains unclear. We hypothesized that when CIC is not mutated, other genes may be inactivated by hypermethylation. Identifying such genes may help to further understand the biology of 1p/19q-codeleted glioma. To test our hypothesis, we utilized a two-stage design. In the discovery stage, 72 IDH -mutated 1p/19q-codeleted tumors were utilized from TCGA (40 CIC mutated, 32 wild-type); all via Illumina 450K methylation array. In the validation stage, 43 IDH -mutated 1p/19q-codeleted tumors were utilized from Mayo Clinic (33 CIC mutated, 10 wild-type); all via Illumina 850K methylation array. All tumors also had TERT promoter mutation. Genome-wide significance (p≤5x10 -8 ) was used in the discovery stage to identify differentially methylated probes between CIC mutated vs wild-type tumors. Seven probes reached significance in TCGA; four validated at pCIC. DLL3, located on 19q, had a mean change in beta value between CIC wild-type and mutated tumors of 0.28 (p=1.29x10 -8 ) and 0.24 (p=0.0024) in TCGA and Mayo, respectively. ETV1, located on 7p, had a mean change in beta value of 0.30 (p=1.37x10 -8 ) and 0.15 (p=0.00011) in TCGA and Mayo, respectively. In the 72 TCGA tumors, we observed an inverse correlation between DLL3 methylation and gene expression amongst CIC mutated and wild-type tumors; -0.42 (p=0.0063) and -0.33 (p=0.069), respectively. There was also an inverse correlation between ETV1 methylation and gene expression amongst CIC mutated and wild-type tumors; -0.68 (pDLL3 and ETV1 was downregulated in CIC wild-type vs mutated tumors (p=0.000027 and 0.0000028, respectively). We confirm that ETV1 has higher gene expression in CIC mutated vs wild-type tumors. Our results suggest that DLL3 expression is inactivated by promoter methylation in CIC wild-type 1p/19q-codeleted oligodendrogliomas; thus, DLL3 may be an alternative target gene on 19q.